OJRNHC 2022
DOI: 10.14574/ojrnhc.v22i2.716
|View full text |Cite
|
Sign up to set email alerts
|

The Rural Profile

Abstract: It has been well-documented that rural communities experience poorer health outcomes than urban or suburban communities. The contribution of various structural and sociodemographic factors to this disparity has been well studied. However, research on the impact of the rural profile on health outcomes is understudied, in part because what it means to "be rural" has not been well defined nor operationalized.Methods: Walker and Avant's traditional concept analysis method was used Findings: The rural profile was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…These responses align with the rural constructs of valuing close community relationships and being wary of outside innovation disrupting the social and economic fabric of the community. 5 , 30 Warr et al suggested that to increase acceptability of telehealth services, communities must be involved in the design, implementation, and evaluation of telehealth technologies. 5 …”
Section: Discussionmentioning
confidence: 99%
“…These responses align with the rural constructs of valuing close community relationships and being wary of outside innovation disrupting the social and economic fabric of the community. 5 , 30 Warr et al suggested that to increase acceptability of telehealth services, communities must be involved in the design, implementation, and evaluation of telehealth technologies. 5 …”
Section: Discussionmentioning
confidence: 99%